Konseling Behavioral Dengan Teknik Relaksasi Untuk Mereduksi Kecemasan Menghadapi Ujian Masuk Perguruan Tinggi Pada Siswa SMA - Islami, Chitra Charisma (Academic Journal of Psychology and Counseling, 2022)
There are various problems faced by students, one of which is anxiety facing college entrance exams. If the anxiety is not immediately reduced, it will have an impact on student performance in taking the exam. This article aims to examine and explain the effectiveness of behavioral counseling with relaxation techniques to reduce anxiety facing college entrance exams in high school students. The research sample involved was students of SMA N (senior high school) 1 Kadipaten who experienced anxiety facing the college entrance exam. The research method used is research and development. The data collection tool uses an anxiety scale that has been validated and tested. Based on the results of calculations using the Wilcoxon test, obtained Asymp. Sig. of 0.028 (p<0.05). Thus, behavioral counseling with relaxation techniques is effective in reducing student anxiety in facing college entrance exams. The results of this study can be input for schools to make relaxation techniques as one of the counseling techniques to reduce student anxiety in facing college entrance exams.